An exploration of a personal-professional developmental programme for pre-registration nurses from a multicultural setting - Cronje, Sarah (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MCur (Interdisciplinary Health Sciences. Nursing Science))--University of Stellenbosch, 2010.